2015
DOI: 10.3389/fcvm.2015.00027
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-3 Promotes a Vascular Smooth Muscle Contractile Phenotype

Abstract: Epidemiological studies have demonstrated the importance of cardiovascular diseases in Western countries. Among the cell types associated with a dysfunctional vasculature, smooth muscle (SM) cells are believed to play an essential role in the development of these illnesses. Vascular SM cells are key regulators of the vascular tone and also have an important function in the development of atherosclerosis and restenosis. While in the normal vasculature, contractile SM cells are predominant, in atherosclerotic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The mechanism of the phenotype switch is complicated and involves multiple factors. Myocardin and caveolin-3 were both identified as the guardians of a vascular smooth muscle contractile phenotype [31,32], whereas miR-143/145 and KLF4 promoted the SMC phenotype switch from a contractile to a synthetic state [12,14,33]. Although various data demonstrated that KLF4 is a key molecule regulating the SMC phenotype switch, the regulation of KLF4 expression is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the phenotype switch is complicated and involves multiple factors. Myocardin and caveolin-3 were both identified as the guardians of a vascular smooth muscle contractile phenotype [31,32], whereas miR-143/145 and KLF4 promoted the SMC phenotype switch from a contractile to a synthetic state [12,14,33]. Although various data demonstrated that KLF4 is a key molecule regulating the SMC phenotype switch, the regulation of KLF4 expression is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Schwencke C et al [30] showed that the adenoviral overexpression of caveolin-1 inhibits smooth muscle cell proliferation and that the expression of caveolin-1 in vivo is significantly decreased in proliferating vascular smooth cells of human atheroma, suggesting that the loss of antiproliferative control by caveolin-1 plays a pivotal role in vascular smooth muscle cell proliferation during atherosclerosis. Furthermore, Gutierrez-Pajares JL et al [31] revealed that caveolin-3 promotes the contractile phenotype of vascular smooth muscle cells and reduces cell proliferation and migration, indicating that downregulating caveolin-3 contributes to atherosclerosis development or restenosis by promoting vascular dedifferentiation. Hence, modulating vascular smooth muscle remodeling is another mechanism through which caveolin regulates atherosclerosis.…”
Section: Caveolin and Phonotypic Changes In Smooth Muscle Cellsmentioning
confidence: 99%
“…The protective effect of H 2 on cell viability was measured by the MTT assay. Lactate dehydrogenase (LDH) activity in the culture medium can indirectly indicate cell death/apoptosis [25,26]. As shown in Figure 2A and 2B, in the DON group, 5 µM DON significantly weakened cell viability (p < 0.05) and increased the release of LDH (p < 0.05) compared to the control group.…”
Section: Effects Of H 2 On Cell Viability and Apoptosis In Don-inducementioning
confidence: 98%
“…Cell culture supernatant was collected to assess lactate dehydrogenase (LDH) release due to cell death/apoptosis [25,26]. Briefly, IPEC-J2 cells (2 × 10 5 cells/well) were grown in six-well plates.…”
Section: Ldh Activity Measurementmentioning
confidence: 99%